Rhetoric of Possibility and Semantic Reinterpretation of Tradition in Two Short-Stories of Luisa Valenzuela’s Cuentos de Hades - Carreón Tapia, Karla Juliana (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Luisa Valenzuela’s collection of short stories Cuentos de Hades (1993) retrieves and reinterprets traditional folktales from what some experts call a feminist perspective. Using a Lausbergian approach, this work aims to reveal how, in these stories, elocutio emerges from rhetorical devices such as questions, ellipses, and anaphora, as well as from syntax and grammar. Therefore, this work reveals the technical mechanisms involved in a statement for the opening of the senses, possibility and transformation of the protagonists. This transformation is achieved through the use of language to challenge and transgress conventional gender roles associated with traditional literature.